Potential of albumin dialysis at terminal liver failure in patients with chronic liver diseases - O. E. Nikiforova; Ye. N. Bessonova; O. M. Lesnyak; O. A. Stroganova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study efficacy of albumin dialysis (MARS) at complications of end-stage liver diseases having various etiology.Material and methods. Overall 65 patients with chronic terminal liver diseases of Child–Pugh B and C classes have been included in original study. The first (main group) included 25 patients, that received albumin dialysis in addition to traditional drug therapy. The second group (comparison group) included 40 patients who received only traditional pharmaceutical therapy. In relation to etiology of disease all patients were divided into three groups: 1) cirrhoses of the nontoxic etiology as an outcome of viral hepatitis, primary biliary cirrhosis, primary sclerosing cholangitis; 2) cirrhosis of toxic (alcohol-induced) etiology and 3) focal liver lesions – hepatocellular carcinoma (HCC).Results. Among patients, receiving treatment with albumin dialysis the stage of hepatic encephalopathy at patients in the subgroup with cirrhosis of toxic (alcohol-induced) etiology significantly decreased (р<0,01). In general the level of biochemical scores of blood at patients after MARS was lower, than at patients who did not receive MARS, however no improvement in AST, ALT activity was found. Study results (triple decrease of bilirubin level and significant decrease of creatinine> <0,01). In general the level of biochemical scores of blood at patients after MARS was lower, than at patients who did not receive MARS, however no improvement in AST, ALT activity was found. Study results (triple decrease of bilirubin level and significant decrease of creatinine contents) testify the greater efficacy of albumin dialysis in subgroup of patients with liver cirrhosis of toxic (alcohol-induced) etiology. At patients with nontoxic cirrhosis (mainly cholestatic), who received MARS-therapy, the majority of whom were in the waiting list of liver transplantation (9 patients), decrease of total bilirubin level was accompanied by decrease of pruritis. In group of patients with HCC no significant decrease of bilirubin level was observed. It is necessary to point, that in none patients MARS was complicated by bleeding or progression of other manifestations of hemorrhagic syndrome.Conclusions. Albumin dialysis in the patients with cirrhosis enrolled to the waiting list of liver transplantation, allows to prolong scheduled interim to liver transplantation that is the extremely important factor, allowing to survive to operation and to decrease mortality in patients with terminal liver failure.